Haloperidol vs. dexamethasone in lowering postoperative nausea and vomiting and pain in adult after laparoscopy: A randomized, double-blind study - Heriwardito, Aldy; Manggala, Sidharta; Widhyanti, Suryo; Aristya, Lara (Bali journal of anesthesiology, 2022)
Background: The incidence of PONV (Postoperative Nausea and Vomiting) and pain are still one of the most common symptoms of post-surgery and prophylaxis to reduce the event is needed. Therefore, we wanted to know the effectiveness of 1 mg intravenous haloperidol compared to 5 mg intravenous dexamethasone to prevent the occurrence of nausea and vomiting and to control pain in adult patients after laparoscopic surgery. Materials and Methods: Eighty subjects (n = 40 for each group) scheduled for laparoscopic-assisted surgery were enrolled in a randomized double-blind clinical trial. One milligram intravenous haloperidol was given one hour before the end of surgery, while 5 mg intravenous dexamethasone was given right after induction. The occurrence of PONV and VAS pain score were recorded. Results: This study showed a significant difference in the incidence of nausea between haloperidol and dexamethasone at 2-6 hours (5% vs 25%, P = 0.012), 6-12 hours (10% vs 24%, P = 0.012), and 12-24 hours (12.5% vs 60%, P < 0.001) after laparoscopic surgery. The incidence of vomiting after laparoscopic surgery between two groups was not significantly different (P > 0,05). However, haloperidol group resulted in lower VAS pain score at every postoperative period with statistically significant result. Conclusion: The administration of 1 mg intravenous haloperidol is significantly better than 5 mg intravenous dexamethasone to prevent the occurrence of nausea and to lower the pain, but not significantly different to prevent the incidence of postoperative vomiting in adult patients after laparoscopic surgery.